2021
DOI: 10.1016/j.frl.2020.101882
|View full text |Cite
|
Sign up to set email alerts
|

COVID−19 and oil price risk exposure

Abstract: Highlights Oil supplier industries are associated with the highest positive exposure to oil price risk Oil user industries exhibit negative exposure to oil price risk COVID–19 appears to moderate oil price risk exposure of industries Oil price risk exposure of industries appears to be similar across regions Results are robust to alternative asset pricing models

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(49 citation statements)
references
References 44 publications
(47 reference statements)
2
37
0
Order By: Relevance
“…The MSCI Global Alternative Energy Index stays for most of its time in the low-volatility regime 2 without being adversely and significantly affected by the COVID-19-related indicators and only once switches to the high-volatility regime 1. Our results correspond to Akhtaruzzaman et al [42] and Corbet et al [44]. Moreover, the results are consistent with the IEA Global Energy Review 2020 [41], which showed that the COVID-19 pandemic did not hamper the alternative energy industry in comparison to the conventional energy sector, and renewable energy sources are the most Covid-19 resilient.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The MSCI Global Alternative Energy Index stays for most of its time in the low-volatility regime 2 without being adversely and significantly affected by the COVID-19-related indicators and only once switches to the high-volatility regime 1. Our results correspond to Akhtaruzzaman et al [42] and Corbet et al [44]. Moreover, the results are consistent with the IEA Global Energy Review 2020 [41], which showed that the COVID-19 pandemic did not hamper the alternative energy industry in comparison to the conventional energy sector, and renewable energy sources are the most Covid-19 resilient.…”
Section: Resultssupporting
confidence: 92%
“…According to IEA [41], renewable energy would still increase, making renewable energy sources the most Covid-19 resilient. Akhtaruzzaman et al [42] claim that oil-substitute industries, i.e., alternative energy, alternative fuels, and alternative energy equipment and infrastructure, have positive exposure to oil price risk, and the level of a vulnerability is much lower than those of oil supply and infrastructure provider industries. The evidence shows that investment in solar and wind energy has not stopped growing through the last oil price mitigation in 2020 as most investment funding in renewables come from outside the conventional energy sector [43].…”
Section: Introductionmentioning
confidence: 99%
“…Regulators have postponed or lifted bans, prohibited consumers from using reusable items (Tenenbaum, 2020), and interrupted recycling services to prevent crosscontamination (Leonard & Mallos, 2020). At the same time, energy demand has plummeted in many sectors, shortly followed by commodity pricesmaking petroleum-based virgin plastic even less expensive (Chaudhuri, 2020;Nyga-Lukaszewska, 2020;Akhtaruzzaman, 2021). While the exact impacts are difficult to quantify as the COVID-19 pandemic is ongoing, the implications are sure to be felt for decades to come.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] As to the oil market, the volatility of oil price increased following the commencement of COVID‐19 [ 4 ] and financial industries responded negatively to positive oil price shocks. [ 5 ] During the pandemic, both oil and stock markets may encounter stronger impacts of their own and cross shocks. [ 6 ] At the firm level, the Covid‐19 pandemic provides enterprises the opportunity to undertake more authentic and genuine CSR [ 7 ] and relevant activities can help hospitality companies enhance their stock returns and gain stakeholders’ attention during the pandemic.…”
Section: Introductionmentioning
confidence: 99%